2018
DOI: 10.1111/1541-4337.12374
|View full text |Cite
|
Sign up to set email alerts
|

Is the Yellow Knight Mushroom Edible or Not? A Systematic Review and Critical Viewpoints on the Toxicity of Tricholoma equestre

Abstract: There is no scientific consensus regarding the safety of the Yellow Knight mushroom Tricholoma equestre (L.) P.Kumm. Following reports of cases of intoxication involving effects such as rhabdomyolysis, and supportive observations from in vivo experimental models, T. equestre is considered as a poisonous mushroom in some countries while in others it is still widely collected from the wild and consumed every year. In this paper, we review all the available information on T. equestre including its morphological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 87 publications
(139 reference statements)
1
21
1
Order By: Relevance
“…The heavy metal contents of the species depend on the ability of the species to extract elements from the substrate, and on the selective uptake and deposition of elements in tissues. The results obtained in the current study, indicated that Pb, Cd, Co, Cu, Mn, Zn and Fe content of the investigated mushroom samples were comparable with those reported in the literature (Table 1) (see [1], [4], [5]). The averages of Pb, Cd, Co, Cu, Mn, Zn and Fe present in the studied wild mushrooms were far below the limits set by the WHO (see [7]).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The heavy metal contents of the species depend on the ability of the species to extract elements from the substrate, and on the selective uptake and deposition of elements in tissues. The results obtained in the current study, indicated that Pb, Cd, Co, Cu, Mn, Zn and Fe content of the investigated mushroom samples were comparable with those reported in the literature (Table 1) (see [1], [4], [5]). The averages of Pb, Cd, Co, Cu, Mn, Zn and Fe present in the studied wild mushrooms were far below the limits set by the WHO (see [7]).…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, deficiency or imbalance of essential or non-essential minerals above threshold concentration levels confers a risk of disease development. Therefore, the adequate and accurate food composition data are essential for estimating the adequacy of intake of essential nutrients and assessing the risk from toxic metals (see [1], [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms are an important food product, which is particularly valued as a delicacy in Asia and Central-Eastern Europe for their taste, nutritional value and biological activity [1][2][3][4][5][6]. Apart from traditional collection of wild mushrooms, there is a growing interest in cultivated forms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms are known to uptake and accumulate various chemical elements [5,[15][16][17][18]. However, the efficiency of this process can be species dependent and can be influenced by bioavailability of elements [4,19].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, it had a long -history of consumption in many countries with no anecdotal or scientific evidence of toxic effects. It is still considered edible and widely consumed in regions such as Poland [8]. As shown in a recent study, more than half of mushroom foragers in this country have consumed T. equestre at least once in their lifetime [9].…”
mentioning
confidence: 99%